Mechanical reverse engineering approach for precise measurements of reproducing disc CAM - S. Alsoufi, Mohammad; W. Alhazmi, Mohammed; Azam, Sufyan (International Journal of Engineering and Technology, 2019)
This research paper focuses on reverse engineering in a mechanical engineering design domain. The paper presents the process of reversed disc CAM from an existing one and also the strategy for scanning and converting the scanned data using coordinate measuring machine (CMM) technology in the form of point cloud data into a 3D model of the disc CAM and finally measurement assessments. The copy of the existing part is in order to produce the original (existing) product design intent. This paper investigates the current aluminum, hardened steel and stainless steel disc CAM and the reversed disc CAM (including aluminum, hardened steel, stainless steel, PLA+, PLA, ABS+ and photo-polymer resin) in terms of the height variation, dimensional accuracy, surface roughness and skewness and kurtosis performance. These are done with the help of various instruments used for data acquisition and different softwareâ€™s used for data processing and modeling. These parameters of assessments have huge influences on the functional behaviour as well as the customersâ€™ quality perception of the products.Â